Influencing organizational decision-makers – What influence tactics are OHS professionals using?. (January 2020) - Madigan, Cassandra; Way, Kïrsten; Capra, Mike; Johnstone, Kelly
Highlights: Influence tactics explain a significant amount of difference in OHS professionals' effectiveness to influence. Rational persuasion and inspirational appeal were more effective in influencing organizational decision-makers. Legitimating and exchange tactics were less effective in influencing organizational decision-makers. Safety maturity levels impacted on the choice of tactics and perceptions of effectiveness. Abstract: Ability to influence within organizations has been identified as a key capability for occupational health and safety (OHS) professionals. By utilising aspects of intra-organizational influence theory, this study explores the specific behaviors that OHS professionals use to influence organizational decision-makers. Survey data was collected from OHS professionals (n = 385) on proactive influence tactics used and the perceived outcomes of influencing attempts. The results show that certain individual factors (i.e. gender, age, OHS experience) and organizational factors (i.e. level of safety maturity and organisation size) impact on tactics used and influencing effectiveness. The use of influence tactics explains a significant amount of variation in OHS professionals' effectiveness in influencing organizational decision-makers, and certain tactics (rational persuasion and inspirational appeal) were positively associated with influencing effectiveness, while others (legitimating and exchange) had a negative association. This study extends existing research in the upward influencing context by exploring how OHS professionals exert influence at a granular level and proposes implications for professional practice.